2021
DOI: 10.1002/asjc.2574
|View full text |Cite
|
Sign up to set email alerts
|

Design of adaptive weld quality monitoring for multiple‐conditioned robotic welding tasks

Abstract: Multiple-conditioned welding monitoring is a challenging issue in complex robotic welding tasks. In practice, the monitoring system has to be sensitive to different welding conditions (WCs) and weld quality changes. In this paper, a swing high temperature sensor system is used in order to obtain the temperature distribution curve under different WCs. A sigmoid feature extraction (SFE) method is proposed to obtain the geometric features of the temperature distribution curve, and a weld monitoring algorithm is p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…At the same time, considering the problem of image noise, a method based on attention dense convolutional blocks is adopted to solve the problem of image noise. Finally, the research model will be applied to specific robot welding scenarios, and the technology studied can accurately extract weld texture features, thereby ensuring the quality of welding robots (Xia et al, 2022) Mikkelstrup et al found that in some complex welding robot work scenarios, traditional welding robots are difficult to effectively ensure the quality of welding. On the basis of digital twin technology, this study focuses on high-frequency mechanical impact treatment.…”
Section: Related Workmentioning
confidence: 99%
“…At the same time, considering the problem of image noise, a method based on attention dense convolutional blocks is adopted to solve the problem of image noise. Finally, the research model will be applied to specific robot welding scenarios, and the technology studied can accurately extract weld texture features, thereby ensuring the quality of welding robots (Xia et al, 2022) Mikkelstrup et al found that in some complex welding robot work scenarios, traditional welding robots are difficult to effectively ensure the quality of welding. On the basis of digital twin technology, this study focuses on high-frequency mechanical impact treatment.…”
Section: Related Workmentioning
confidence: 99%